Boswellic acid – Medicinal use of an ancient herbal remedy - Vuddanda P.R.; Singh S.; Velaga S. (My University, 2025)
Boswellic acid (BA) is an ancient herbal drug prescribed in the Indian traditional medicine systems (Ayurveda) for treatment of coughs, colds, hoarseness, bronchitis, asthma, dyspnea and diarrhea. Current research suggests it also has therapeutic potential in modern medical practice. Therefore, it is of interest to the research community to consolidate the preclinical and clinical findings on BA. The aim of this review was to comprehensively cover the plant sources, phytochemistry and physicochemical properties of BA along with its medicinal properties, safety, toxicity, and regulatory status. The review also discussed the challenges associated with drug delivery and some feasible approaches for addressing these. Four electronic databases (Scifinder, Unbound Medline, PubMed and Science Direct) and two internet search engines (Scirus and Google Scholar) were extensively searched without any time constraint. The many studies discussed in the review indicated therapeutic potential for BA in the treatment of a range of chronic diseases including arthritis, cancer, asthma and diabetes. It is hoped that this review will help researchers identify relevant research questions leading to the development of effective formulations and a better understanding of the safety of BA, with the aim of promoting it as a mainstream treatment for various diseases in clinical practice. © 2016 Elsevier GmbH